(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the characteristics of malnutrition from birth to 10 years of age among full-term children in Thai Nguyen province. Subjects and Methods: A cohort study was conducted on 703 full-term children with birth weights ≥ 2500g, born from 2012-2013 in 20 communes across 4 districts (midland and mountainous areas) of Thai Nguyen province. Anthropometric data were collected at 9 time points from birth to age 10. Nutritional status was classified according to WHO (2006) standards for children 0-5 years and WHO (2007) standards for children 5-19 years. Results: The prevalence of stunting increased rapidly during the first 24 months, peaking at 24 months (22.8% in girls, 17.2% in boys), and then declined at ages 6 and 10. Underweight peaked at age 6, while wasting was most prevalent at birth and dropped below 3% at later time points. The prevalence of overweight/obesity rose again at age 10, particularly in boys (20.3%). Conclusion: Full-term children remain at risk of malnutrition, especially during the first 1000 days of life and early primary school years. The study provides important evidence for monitoring growth and designing age and sex-appropriate nutritional interventions.